The feminine narration of masculine patterns in some passages of "History is ripped apart in the body of women" by "Adonis". - Borhom, Ltfieh Ibraheem; Mostafa, Mohmmed Hassan (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Cultural criticism focuses on eradicating and deconstructing the dominance patterns . This research tries to re-interpret the biography of divine in the female lens , the oppressed pattern , the oppressor one , that advocate the masculinity of culture ; to finally reveal the hidden one, in which the women hood tries to describe and go in deep in its cases , that tackle the female body the axis of existence in its relation to divine and masculinity. To conclude , the feminine re-write the masculinity through re-forming the criteria between : margin: feminine and center: masculinity . It also utilize the feminine vision which does not eradicate the oppressor masculine pattern , interacting or melting in , but it chooses the humanity tendency that overriding any denied ideology. انطلاقاً من أن النقد الثقافيّ يركّز على استخلاص الأنساق المُضمرة وتفكيكها ، فإنّ البحث يحاول استقراء سيرة المقدّس على لسان الأنثى ؛ سيرة النسق المقموع ، والنسق القامع المُنتصر للثقافة الذكوريّة المتأصّلة، وصولاً إلى النسق الغائب الذي تحاول الأنوثة وصفه، والغوص في مكوّناته التي تتّخذ من الجسد الأنثويّ محوراً للامتداد الوجوديّ من خلال علاقته بالمُقدّس و الذكوريّ. يخلص البحث إلى أنّ الأنوثة تُعيد كتابة الذكورة بصوغ المعادلة بين هامش أنثويّ ومركز ذكوريّ ، وتوظيف الرؤيا الأنثويّة التي لا تريد خلع الذكوريّ القامع، أو الحلول به ،أو التماهي معه ؛لتخيّرها النزعة الإنسانيّة المنزّهة عن أيّة أيديولوجيا تُدين كلا الطرفين .